2003
DOI: 10.1017/s1047951103000519
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic sequels after thoracotomies in children with congenital cardiac disease

Abstract: a relatively common surgical approach for closed procedures in infants and children with congenital cardiac malformations. This approach results in division of the latissimus dorsi and serratus anterior muscles. Division of these muscles can result in significant postoperative pain, diminished pulmonary function, and marked impairment of motion.The thoracotomy incision may also result in longterm physical impairment and deformity. Scoliosis has been reported to develop with an incidence of 22% several years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…Some authors favor a non-operative attitude considering the risks and eventual complications of a thoracotomy [7], with lung resection, and the possibility of spontaneous resolution in some cases [3,4]. Postnatal imaging studies have shown that regression is rare in the cystic type lesions [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors favor a non-operative attitude considering the risks and eventual complications of a thoracotomy [7], with lung resection, and the possibility of spontaneous resolution in some cases [3,4]. Postnatal imaging studies have shown that regression is rare in the cystic type lesions [5].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary lobectomy via a posterolateral thoracotomy incision has been the standard surgical procedure. The associated morbidity of this approach in small infants has even questioned the need of resection itself [7]. In the recent years, thoracoscopy (VATS) has become an increasingly important tool in pediatric surgery and, as technology improves, more technically demanding procedures can be performed in small children [6,[8][9][10][11]].…”
Section: Introductionmentioning
confidence: 99%
“…This incidence would be higher, if the follow-up time could be longer. Patients who have undergone such procedures for cardiac or noncardiac surgery should be followed until their skeletal maturation is complete [9]. A computerized tomography based study demonstrated that severe unilateral atrophy of latissimus dorsi muscle ipsilateral to the operative side was due to denervation injury [10].…”
Section: Discussionmentioning
confidence: 99%
“…The principal advantage of thoracoscopy over thoracotomy [4] is reduced postoperative pain, shorter chest tube duration, shorter hospital stay, and better cosmetic results. The main benefit is the reduction of long-term morbidity [13] including scoliosis, shoulder weakness, and chest wall deformity.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage is reduced long-term morbidity [4,13], namely, a lower incidence of scoliosis, shoulder weakness, and chest wall deformity.…”
mentioning
confidence: 99%